Entangled hagiographies of the religious other - Cuffel, Alexandra; Jaspert, Nikolas (Cambridge Scholars Publishing, 2019)
On entangled hagiographies : perspectives and results / Nikolas Jaspert -- Christian hagiography as anti-pagan polemics : conceptions of interreligious encounter in the "Passio Viti" (7th century) / Gregor Rohmann -- Salvaging the saintly Sergius : hagiographical aspects of the Syriac legend of Sergius Baḥīrā / Barbara Roggema -- The early Laozi and the "other" : notes on early narratives and demarcation / Licia Di Giacinto -- Historical entanglements or a static image? The life of Muhammad in Gerald of Wales's de Principis Instructione / Matthew Mesley -- Conversion reports as mirrors of encounter with the religious other? The case of the Anatolian Persian Muslim hagiography Manāqib al 'firīn of Aḥman Aflāk / Şevket Küçükhüseyin -- Triple entanglement : a Christian anti-biography of Muhammad in a Jewish anti-Christian polemic / Alexandra Cuffel -- Long story : "Barlaam and Josaphat", "Physiologus" and their influence on a Wallachian Speculum Principis from the 16th century / Mihai Grigore -- The ritual visualization of the saint in Jewish and Muslim mysticism / Paul B. Fenton.